2017
DOI: 10.1371/journal.pone.0169545
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Iron Storage Proteins in Maintaining the Iron Homeostasis in Mycobacterium tuberculosis

Abstract: Ferritins and bacterioferritins are iron storage proteins that represent key players in iron homeostasis. Several organisms possess both forms of ferritins, however, their relative physiological roles are less understood. Mycobacterium tuberculosis possesses both ferritin (BfrB) and bacterioferritin (BfrA), playing an essential role in its pathogenesis as reported by us earlier. This study provides insights into the role of these two proteins in iron homeostasis by employing M. tuberculosis bfr mutants. Our da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 36 publications
(54 reference statements)
1
60
0
1
Order By: Relevance
“…The host uses the oxidative stress to combat infection by pathogenic micro‐organisms, and it has already been reported that bacterioferritins provide a key mechanism of protection against this host defence (Khare et al ). To determine if the presence of recombinant bacterioferritin reduced the harmful effects of oxidative stress, Mycma_BfrA and Mycma strains growth were analysed in MM supplemented with 50 µmol l −1 of FeCl 3 containing various concentration of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The host uses the oxidative stress to combat infection by pathogenic micro‐organisms, and it has already been reported that bacterioferritins provide a key mechanism of protection against this host defence (Khare et al ). To determine if the presence of recombinant bacterioferritin reduced the harmful effects of oxidative stress, Mycma_BfrA and Mycma strains growth were analysed in MM supplemented with 50 µmol l −1 of FeCl 3 containing various concentration of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The importance of bacterioferritins in the virulence and pathogenicity of Mycobacterium remains unclear, although some studies have proposed a role of this protein in the iron homeostasis of the bacillus (Pandey and Rodriguez ; Reddy et al ; Khare et al ). The influence of bacterioferritin during host infection was suggested to be dispensable, as mutants for this protein presented similar behaviour to the parental strains in different models of infection (Pandey and Rodriguez ; Reddy et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under stationary phase stress, Msm encapsulin appears to primarily enclose DyP, a potent protein antioxidant (14). The main role of BrfB, another potential encapsulated protein, is to relieve iron toxicity (26). EM models provide a good indication of the relative abundance of binding partners in a protein complex; more abundant members will dominate the density (7,27).…”
Section: Discussionmentioning
confidence: 99%